THE EFFECT OF PROBLEM BASED LEARNING MODEL AND DISCOVERY LEARNING TOWARD PROBLEM SOLVING SKILLS IN MATHEMATIC OF GRADE 5 ELEMENTARY - Dwi Setyo Rini; Wasitohadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this research is to know about implementation of influence PBL and DL model to Mathematic Problem Solving for 5th grade student at elementary school. The type of this research was Quasy Experiment. The result of prerequisite test by using SPSS 25 for windows showed that the data was distributed in normal and homogeny. The independent sample test result showed the significant 0.000 < 0.05 that meant Hₒ was rejected and Hₐ was accepted. Based on the result obtained, there are significance difference in the implementation between PBL and DL models toward Mathematic Problem Solving ability in 5th grader elementary school students, and there was a significant difference of improvement toward Mathematic problem solving ability in 5th grade elementary school students which can be seen from the comparison of diagram that using PBL had more influence with pretest result 69% and posttest 80%, while using DL model result pretest 66% and posttest 73%.